Threshold effects of fiscal decentralization on income inequality: Evidence from Vietnam - Nguyen Thanh Hung; Su Dinh Thanh (Cogent Business & Management, 2022)
This paper proposes a new approach to analyse the dynamic relationships between Fiscal decentralization and Income inequality of 63 provinces/cities of Vietnam in the period from 2000 to 2018, with the the Panel smooth transition regression (PSTR) model for estimating the threshold impact of fiscal decentralization on income equality through economic growth. The empirical results obtained from the analysis show strong and unequivocal evidence on the different effects of fiscal decentralization variables (ED1, ED2, RD1, RD2, TD) on income inequality, according to each stage of local growth. Additionally, in their relationship with inequality, the variables ED1, ED2, and FDI react quite sensitively to the change of income levels of the economy around the threshold value of VND78.33 million VN/person/year. Thus, our study contributes to the theory a new insight into the mixed results regarding the nonlinear relationship between fiscal decentralization and income inequality, based on which an effective strategy can be drawn up to reduce income inequality within the country.
Keywords: 650; Income inequality; growth; PSTR; threshold of fiscal decentralization